Pelatihan Teknik Pengambilan Gambar Video Kebaktian Secara Daring Di Vihara Buddha Gaya Bandung - Yapinus, Pin Panji; Wijaya, Marvin Chandra; Tjiharjadi, Semuil; Loekito, Jimmy Agustian; Wong, Hendry; Lehman, Andrew Sebastian; Tanubrata, Markus; Chandra, Jonathan; Karsen, Leon; Cahyadi, Tonny; Tan, Gary (Universitas Nusantara PGRI Kediri, 2023)
Due to the Covid-19 pandemic, some houses of worship have to carry out worship activities online. The obstacle is the human resources in a house of worship who do not yet have the ability or are accustomed to conducting online services. One of the materials that can be taught is the direction of taking online devotional videos. Through this training, it is hoped that the youth at the Vihara Gaya Buddha Bandung organization can add insight and expertise in the creation of online devotional video content. The method used is to combine online and offline training. The online method is used when viewing and learning the needs needed for training activities. The offline method provides hands-on training on how to take videos properly and correctly. The result of the training is an online service production at Vihara Buddha Gaya, Bandung. The training materials are divided into two categories, namely shooting techniques and sound systems. The success of this training was measured by conducting practical tests to assess the results of the two categories. The results of the practical test assessment showed that the training participants had 100% success in making online devotional videos properly and correctly.